Sensing of Transition Metals by Top-Down Carbon Dots - Federico Bruno (MDPI AG, 2021)
Carbon quantum dots (CQDs) are a new class of carbon-rich materials with a range of unique optical and structural properties. They can be defined as carbon nanoparticles, with sizes in the range of 1–10 nm, displaying absorption and emission activities in the UV-VIS range. Depending on the structure, CQDs display a wide variability of properties, which provides the possibility of finely tuning them for several applications. The great advantages of CQDs are certainly the ease of synthesis, non-toxicity, and the strong interactions with the surrounding environment. Based on this, CQDs are especially promising as selective chemosensors. The present study reports on carbon quantum dots synthesized with a top-down (TD) approach, and characterized by different optical, spectroscopic, and morphological techniques to identify the selectivity for metal ions belonging to the first transition series. In particular, the study focuses on the interaction between two samples, namely TD and TDA, featuring different surface functionalization, and heavy metal ions. Their sensing towards Co2+, Cu2+, Fe3+, Zn2+, and Ni2+ has been tested by fluorescence (PL), steady state absorption spectroscopy, and time-resolved PL spectroscopy, in order to determine the fluorescence quenching. We found a PL quenching in the presence of concentrations of metal salts starting from 0.5 µM, and a selectivity towards the interacting ions, depending on CQDs’ surface features paving the way for their use for sensing.